The case of #NeverAgainMSD: When proceduralist civics becomes public work by way of political emotion. (3rd April 2019) - Knight Abowitz, Kathleen; Mamlok, Dan
ABSTRACT: Civic culture is a term for how citizens actively live out, perform, and create public life through our habits, actions, words, and public work. A vital civic culture, with an engaged citizenry, is one of the measures of a healthy democratic republic. In this inquiry, we explore how civic education—holistically envisioned across disciplines and types of curriculum—might be imagined in light of civic cultural engagement and creation. We use the recent #NeverAgainMSD youth activism against gun violence as a single case study through which to examine what educators can learn from youth enacting citizenship in real time, contributing to a vital civic culture in an era when many lament youth apathy and disconnection from public life. We argue that much civics education ignores the worth of political emotion, and we describe both the important role of affect in civic culture and curricular possibilities for working with students around the intersections of affect, civic culture, and public work as citizens.